A Selective Near‐Infrared Fluorescent Probe for In Vivo Imaging of Thiophenols from a Focused Library. Issue 24 (22nd November 2016) - Pan, Yue; Ren, Tian‐Bing; Cheng, Dan; Zeng, Ze‐Bing; Yuan, Lin; Zhang, Xiao‐Bing
Abstract: Thiophenols are highly toxic industrial materials that, once released, will accumulate in the environment, and ultimately in human bodies, thereby causing serious health problems. To achieve their selective and sensitive detection, a novel near‐infrared (NIR) fluorescent probe (CCP‐1 ) from a focused library was developed for thiophenol species. Our studies show thatCCP‐1 displays a thiophenol‐triggered 28‐fold fluorescence intensity enhancement at 706 nm, with a detection limit of 34 nm observed. It is also able to differentiate thiophenols from various other thiol‐containing analytes including hydrogen sulfide, hydrogen persulfide, and aliphatic thiols. In total, the desirable properties (e.g., excitation/emission in the NIR region, good cell‐membrane permeability, intracellular stability, and low cytotoxicity) makeCCP‐1 a potential candidate for thiophenol detection both in vitro and in vivo. In addition, CCP‐1, for the first time, successfully visualized thiophenols in mice models of thiophenol inhalation. Abstract : Bright idea ! Owing to its many desirable properties, such as excitation/emission in the near‐IR region, good cell‐membrane permeability, intracellular stability, and low cytotoxicity, CCP‐1 is a potential candidate for thiophenol detection both in vitro and in vivo. In a model study, thiophenol was successfully visualized in living animals for the first time (see scheme).